Outcome of Percutaneous Nephrolithotomy (Pcnl): Initial Experience in Rajshahi - Bari, Md Abdul; Arefin, Md Moshiur; Islam, Md Tafiqul; Asaduzzaman, Md; Rahim, Md Abdur; Sarker, Abul Kashem (Bangladesh Journal of Urology, 2023)
Objective: To assess the efficacy and safety of PCNL in the treatment of renal stone in Rajshahi. Patients and methods: The study was conducted in the department urology of Rajshahi medical college hospital from December 2016 to August 2021. Five hundred consecutive patients of Nephrolithiasis treated with PCNL were included in this study. Patients of Nephrolithiasis aged 18 years and above of both sex, with no bleeding disorder and fit for general anesthesia were treated with percutaneous nephrolithotomy. After PCNL patients were followed up for 3 months. Outcome was measured with stone clearance, blood transfusion, transient fever, UTI, urine leakage, other organ injury and hospital stay. Descriptive statistics was used to present the data. Result: Mean age of the patients was 40.46±10.64 years and mean size of the stone was 22± 8.50 mm. Stone clearance rate was 92.6% and residual stone was 7.4% cases. Overall complications were recorded in 26.60% cases. Hospital stay was 4.6±1.40, days. Conclusion: PCNL is a safe and effective procedure of renal stone surgery with few complications and short hospital stay. Bangladesh J. Urol. 2023; 26(1): 3-8